Rangordningens inverkan på beteendet hos nötkreatur (Bos taurus) och dess konsekvenser för djurtillsynen - Martikainen, Pia (SLU/Dept. of Animal Environment and Health (until 231231), 2006)
Extensively kept animals for meat production have the right to live in a good environment. Cattle (Bos Taurus) as social animals live in small herds in the wild. When holding animals extensively new problems have arisen regarding human – animal interactions. One welfare problem is to be able to come close enough to the animals to investigate their health condition. The aim with this study was to see if rank order influenced the animal's behaviour and whether or not it influenced the time to approach the test-person, how close the animals came, when they paid attention to the test-person, their flight distance, pace and if the test-person could touch the animals. This study included eight groups of animals of varying group-size. The animals were studied for five consecutive days in April 2006. Four animals in every group were studied; two high ranked cows and two low ranked. Rank order influenced in which pace the animals left the test-person. The pace was calmer on day 5 than on day 1 (p=0,007, Anova) for the low ranked animals. The flight distance was shorter on days 3, 4 and 5 for low ranked animals when the results for days 1 and 2 compared with days 3 -5 (p=0,008, Wilcoxon). There was a tendency that flight distance was shorter for the high ranked animals (p=0,055). Between days 2 and 3, the low ranked animals changed their behaviour. They significantly shortened their distance to the test-person when comparing days 1 and 2 with 3-5 (p<0,001, Anova), time to approach (p<0,001, Anova), the distance where they paid attention (p=0,024, Anova) and if the test-person could touch the animals (p<0,001, Anova). When testing the behaviours vs. group size effect there were positive significant correlations within the high ranked cow groups. When group size got bigger, the time to come close to the test-person got longer (p=0,003, Linear regression=LR), the distance to the test-person got longer (p<0,001, LR), distance when the animal paid attention to the test-person got longer (p=0,001, LR) and there was also a tendency for a difference in which pace the high ranked cows left the test-person (p=0,055, LR). Both group size and training of the animals influenced the animals' behaviour when doing the inspection. Since some of these factors are easy to influence, the animal keeper could do the inspections easier and better.